The Construction Path and Protection Measures of Wetland Park from the Perspective of National Participation in the New Era. (16th August 2022) - Li, Liping; Li, Lifen
Abstract : In order to study many problems, such as unreasonable wetland protection, development, and utilization, resulting in a large reduction of wetland area, and so on, with the rise of the construction and research upsurge of the municipal wetland park, a method of wetland park construction path and protection measures based on the perspective of the new era of national participation was proposed. This method takes the construction of urban wetland parks as the research object, starts with the actual demand for wetland parks from the perspective of urban residents' health in the new era, and discusses the construction path and related protection measures of wetland parks from the perspective of national participation. The results show that urban wetland park is an important green infrastructure in the region. In addition, it should have elastic adaptability, complex benefits, and special regional characteristics, to create an elastic dynamic system that can adapt to changes in planning and design, improve social public service functions, set up public access points, stimulate media benefits, and integrate regional characteristics.